Social Capital, Joint Responsibility Systems, And Empowerment Of Women In Msmes : A Conceptual Framework - Anni Yudiastuti; Heri Pratikto; Sopiah (International Journal of Science, Technology & Management, 2021)
Empowering women, especially in entrepreneurship, is often faced with limited accessibility, especially in meeting capital through loans at formal financial institutions and structural constraints in their environment. Women's cooperatives are a bridge to overcome the problem of women's entrepreneurial capital to increase their business, because basically woman have potential in its business activities. Social capital that has elements of Trust, Network and norms attached to women's personalities will be a guarantee in obtaining loans with a joint responsibility system. The opportunity to develop a business through social capital and joint responsibility has an impact on opening up opportunities to empower micro, small and medium entreprise (MSMEs) business actors to further increase their business and continue to be in a sustainable entrepreneurial position.Sustainable Entrepreneurship for female entrepreneurs offers women professional development and limited flexibility to balance work and family commitments.